Kode Vicious: Obvious Truths. - Neville-Neil, George V. (Communications of the ACM, 2009)
In this article the author discusses computer science, examining how to manage computer software projects that are behind schedule and the manner in which computer code is patched, compiled, and tested. When a software development project continues to be extended, or there is a loss of control over the project, one should consider stopping the project, the author indicates.